Genetic Variability in Yard Long Bean (Vigna unguiculata subsp. sesquipedalis (L.) Verdcourt - Resmi PS (Department of Horticulture, College of Agriculture, 1998)
Thirty yard long bean genotypes varying in morphological traits collected from the southern parts of Kerala were evaluated in an RBD with three replications in the Department of Horticulture, College of Agriculture, VelJayani during 1996-97. The objective was to assess the variability existing in the germplasm in yield, yield attributes, morphological characters and pest and disease resistance and to identify suitable lines for further breeding programmes. Variability analysis revealed significant difference among the genotypes for all the characters studied. GCV and PCV were highest for pod yield per plant followed by pods per kg. High heritability coupled with high genetic gain was observed for pod yield per plant, pods per kg, inflorescence per plant, pod weight and keeping quality of pods. ~ Pod yield per plant was strongly associated with pod weight, pod length, pods per kg and pods per plant. Path analysis revealed that the primary yield contributors were pods per plant followed by pod weight owing to their high positive direct effects. Genotypes VS-6 and VS-11 recorded the maximum selection index scores and the minimum was for VS-16 followed by VS-I O, Mahalanobis D2 analysis could group the genotypes into four clusters, cluster TV being the largest with 18 genotypes with the highest intrac1uster 02 value. Cluster 1 and III were the most distant clusters and the genotypes belonging to these clusters can be utilized in hybridisation breeding Genetic catalogueing of the genotypes were made using standard dcscriptors Association between flower colour, stem colour, pod pigmentation and seed colour was noticed.